HUKUM ISLAM DAN MULTIKULTURALISME DI INDONESIA - Fitriyani Fitriyani (IAIN Ambon, 2017)
Multiculturalism is a philosophy sometimes interpreted as an ideology that calls for the unity of the various cultural groups with political rights and social status are the same in modern society. The term multicultural is also often used to describe the unity of all ethnic groups of different communities within a country. Multiculturalism is derived from two words: multi meaning many or diverse and cultural meaning of culture or cultures, which etymologically means cultural diversity. Cultures must be understood, is not a culture in the strict sense, but must be understood as all human dialectic on his life. This dialectic will give birth to many faces, such as history, reasoning, verbal culture, language and so forth. The concept of multiculturalism in Islamic law portrayed in QS. al-Hujurat (49): 13.